Strengthening India-Nepal economic relations - Nisha Taneja; Shravani Prakash; Samridhi Bimal; Sakshi Garg; Riya Roy (Indian Council for Research on International Economic Relations (ICRIER), 2019)
India and Nepal have traditionally shared a unique relationship of friendship and economic cooperation. The relationship is characterized by an open and people-friendly border and is built on shared historical, cultural, linguistic, ethnic links between people residing in India and Nepal. With Nepal being a priority under India "Neighborhood First" policy, strengthening the economic relationship holds immense significance and potential for both the countries. India is Nepal's largest export market, the biggest source of its imports and the top investor of foreign capital stock. India also provides Nepal transit facility through its territory to access sea ports for trading with rest of the world. Given this, the main objective of this paper is to suggest policy measures which can increase bilateral trade and investment between India and Nepal. We analyse the bilateral trade patterns and estimate the maximum additional trade potential. We discuss a wide range of issues of importance pertaining to bilateral trade, including tariffs, levy of an agricultural reform fee, under-utilization of the tariff rate quota, non-tariff measures, issues related to ROO and physical barriers to cross-border movement of goods. We also analyse the trend and changing sectoral composition of India's investment in Nepal. We discuss barriers and opportunities for Indian investment in Nepal. The paper concludes by charting a way forward for bolstering economic cooperation between the two countries by listing down recommendations for enhancing trade, addressing non-tariff barriers, upgrading infrastructure to improve connectivity and enhancing Indian FDI in Nepal.
Keywords: F10; F13; F15; F50; F53; P45; 330; India-Nepal; Bilateral Trade; Bilateral Investment; Trade in Services; Non-Tariff Barriers